Testing protocol for quantitative comparison of top of the range soccer boots - Ronkainen, J.; Toon, D.; Santry, J.; Waller, T. (The Engineering of sport 7, Volume 1, 2008)
Soccer manufacturers are spending increased amounts of time and money developing their soccer boots. Claims such as more grip, more control and more speed have been used in advertising campaigns and no doubt will be used again in the future. The proof behind such claims is often not realistic to match play situations therefore this investigation set out to compare three top of the range branded boots and one pair of prototype boots using University level players to strike an instep swerving free kick. Subjective player feed-back was given regards to the comfort and feel of each boot and how it felt to strike the ball. Objective results were obtained for each strike using a soccer launch monitor, used to measure the launch characteristics for each kick, allowing a direct measure of ball velocity, launch angle and spin rate. Player testing was used in order to achieve feedback on the boots, this presented an inherent problem of inconsistent strikes. Therefore ten repeats of each kick were carried out and no miss kicks were recorded. Since soccer is predominantly played outdoors, the weather conditions can drastically influence the players kicking ability. In wet conditions an aquaplaning effect is observed when the boot contacts the ball reducing the amount of grip between boot and ball. Therefore it was vital to test the boots in wet and dry conditions. The results obtained showed clear trends, in the wet conditions less spin and less velocity were imparted on the ball. No significant differences were observed between the launch characteristics measured between the different boots, suggesting that boots performed similarly, however distinguishing factors such as comfort, feel, aesthetics and branding were deemed very important by the players.